2004
DOI: 10.1007/bf02344639
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the third heart sound using a tailored wavelet approach

Abstract: The third heart sound is normally heard during auscultation of younger individuals but disappears with increasing age. However, this sound can appear in patients with heart failure and is thus of potential diagnostic use in these patients. Auscultation of the heart involves a high degree of subjectivity. Furthermore, the third heart sound has low amplitude and a low-frequency content compared with the first and second heart sounds, which makes it difficult for the human ear to detect this sound. It is our beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…While we do not directly prove that the reported fluctuations are responsible for the S 3 bruit, extrapolation from our results would support a cause-and-effect relationship 46 . Indeed, the present time-frequency analysis showed consistent results regarding a) the S 3 main frequency content previously reported 22 (10-100 Hz) as well as b) the time window when the most intense fluctuations occurred 11,22 (120-200 ms). These observations support the fact that the hemodynamic fluctuations reported in this paper are a plausible physical explanation for the S 3 bruit.…”
Section: Relationship With Previous In Vivo Measurementssupporting
confidence: 91%
See 1 more Smart Citation
“…While we do not directly prove that the reported fluctuations are responsible for the S 3 bruit, extrapolation from our results would support a cause-and-effect relationship 46 . Indeed, the present time-frequency analysis showed consistent results regarding a) the S 3 main frequency content previously reported 22 (10-100 Hz) as well as b) the time window when the most intense fluctuations occurred 11,22 (120-200 ms). These observations support the fact that the hemodynamic fluctuations reported in this paper are a plausible physical explanation for the S 3 bruit.…”
Section: Relationship With Previous In Vivo Measurementssupporting
confidence: 91%
“…It is worth noting that any CFD study where flow instabilities are not properly represented cannot address the prevalence of ventricular bruits and murmurs 31,46 . Among the sounds usually reported, the S 3 bruit is a low-frequency brief sound harbouring a main frequency content in the range of 10-100 Hz 22 and occurring at the end of the E wave, 120-200 ms after the start of the diastole 11,22 . Although the genesis of this sound is controversial, it is widely reported that "vibrations" occurring during the deceleration of the E wave generate this sound 20,27 .…”
Section: Relationship With Previous In Vivo Measurementsmentioning
confidence: 99%
“…S3 and S4 heartsounds are an early abnormality in heart failure patients, yet difficult to hear and frequently missed by healthcare providers due to their frequency characteristics [4]. However, S3 and S4 sounds may be detectable by CAA, leading to potentially better outcomes via earlier medical intervention [16]. Furthermore, serial evaluation via CAA, even at home, could guide individualized, real-time therapy decisions.…”
Section: Background and Significancementioning
confidence: 99%
“…Much of the previous PCG literature has focused on automatic sound analysis and murmur analysis assuming accurate PCG segmentation, such as in [1], [2], [6], [14], [15], [16], [17], [18], [22], [24], [25], [27], [29], [31], [36], [37], [46], [47], [48], [54], [62], [65], [66], [69], [70]. Many of such previous works rely on accurate PCG segmentation.…”
Section: Review Of Previous Phonocardiogram Segmentation Researchmentioning
confidence: 99%